PRÁTICAS EDUCATIVAS ANTIRRACISTAS NA EDUCAÇÃO INFANTIL: um estudo na Unidade de Educação Básica (UEB) Sofia Silva em São Luís do Maranhão - SANTOS, Dayse Costa dos (2023)
This research deals with the anti-racist educational practices of teachers in early childhood education, focusing on the school Unidade de Educação Básica (UEB) Sofia Silva school, belonging to the municipality of São Luís (MA). It developed from the following problematizing question: how can the educational practices of early childhood education teachers contribute to an anti-racist education? So, the general objective of the research emerged, which is investigating the anti-racist educational practices of early childhood education teachers in order to develop a notebook with didactic and pedagogical guidelines based on law n°. 10.639 / 2003 at the Unidade de Educação Básica Sofia Silva. To achieve the research objectives, the work was divided in three chapters: bibliographic, empirical, and a proposal for applicability. In the bibliographic part, we described children's education in Brazil, the institutionalization of early childhood education, and teacher training for Ethnic-Racial Relations. In the empirical part, we discussed the characterization of UEB Sofia Silva, the methodology of the research, and the results with the analysis and interpretations of the research subjects. The methodology, pplied nature, with a case study as the procedure method, a qualitative approach, and non-participant observation and semi- structured interviews with early childhood education teachers as data collection techniques. The results were organized into response tables and analyzed based on the theoretical framework, which made it possible to understand that practicing na anti-racist education is a challenge, because requires a deep change about how we think, relate, and teach, and that teachers need to deepen their knowledge on the subject for a better understanding. Afterwards, a proposal for an educational product was presented, through the Didactic Guidelines Notebook, with the name: "Anti-racist educational practices in early childhood education based on the law n°. 10.639 / 03", it contains playful strategies for early childhood education, such as games, storytelling, as well as the incorporation of narratives that bring black people as protagonists for teachers using within their realities in the classroom. We conclude, based in research materialized in the Didactic Guidelines Notebook, the work has a strong contribution as an ethnic and cultural instrument of the Afro-Maranhense population, which can be inserted in school spaces in compliance with law n°. 10.639/03.